2018
DOI: 10.1177/1744806918793232
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine attenuates cancer-induced bone pain via suppressing microglial JAK2/STAT3 and neuronal CAMKII/CREB cascades in rat models

Abstract: Cancer-induced bone pain is one of the most severe types of pathological pain, which often occurs in patients with advanced prostate, breast, and lung cancer. It is of great significance to improve the therapies of cancer-induced bone pain due to the opioids’ side effects including addiction, sedation, pruritus, and vomiting. Sinomenine, a traditional Chinese medicine, showed obvious analgesic effects on a rat model of chronic inflammatory pain, but has never been proven to treat cancer-induced bone pain. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 74 publications
2
30
1
Order By: Relevance
“…10D). Our pervious study has already demonstrated that JAK2/STAT3 was mainly colocalized to microglia in the nociceptive pathway [38]. Furthermore, we assessed the effects of STING on activation of JAK2/STAT3 using BV-2 cells, demonstrating that STING activation could increase the phosphorylation level of JAK2/STAT3 signal in microglia.…”
Section: Early C-176 Administration Attenuated Pain Hypersensitivitymentioning
confidence: 84%
“…10D). Our pervious study has already demonstrated that JAK2/STAT3 was mainly colocalized to microglia in the nociceptive pathway [38]. Furthermore, we assessed the effects of STING on activation of JAK2/STAT3 using BV-2 cells, demonstrating that STING activation could increase the phosphorylation level of JAK2/STAT3 signal in microglia.…”
Section: Early C-176 Administration Attenuated Pain Hypersensitivitymentioning
confidence: 84%
“…The NMDA receptor-gated channel regulates calcium influx in the postsynaptic membrane (10,42). Intracellular calcium influx leads to the activation of calmodulin, further activating a variety of signaling pathways, which serve important roles in pain transmission (12,13), including the p38-mitogen-activated protein kinase signaling pathway (46). Therefore, synaptic structure and functional adaptation is an important step in the development of central hyperalgesia (43,44,46).…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of certain molecules in the central and peripheral nerves can cause hyperalgesia in rats with ciBP (10,11). For example, the phosphorylation of calmodulin can activate a variety of signaling pathways to promote inflammatory factors (12,13). oXY, a G protein-coupled receptor agonist, inhibits adenylate cyclase activity, thereby inhibiting caMP production which affects the phosphorylation of membrane proteins (14).…”
Section: Introductionmentioning
confidence: 99%
“…The CIBP model was carried out by inoculating Walker 256 mammary gland carcinoma cells into the right tibia based on previous studies (Chen et al, 2018;Zhou et al, 2018). After anesthesia with pentobarbital sodium (50 mg/kg), a minimal incision in the right leg was made to expose the tibia.…”
Section: Cancer-induced Bone Pain Modelmentioning
confidence: 99%